Re-Evaluating Competence to Stand Trial - Collins, David (2018)
The current federal law governing a defendant’s competence to stand trial is substantially contained in 18 U.S.C. § 4241 that can be traced to a 1949 statute and, in Dusky v. United States, a three paragraph opinion of the Supreme Court, delivered in 1960. The federal statute was initially drafted by a committee of the Judicial Conference of the United States. Thus, material aspects of the federal tests for assessing a defendant’s competence to stand trial were composed by federal judges. This paper explains why the current federal law concerning a defendant’s competence to stand trial is antiquated and no longer fit for purpose. The deficiencies in the current law primarily stem from the fact that the legislative test is confined to defendants who suffer a “mental disease or defect” that renders them incompetent and fails to address the circumstances of defendants whose incompetence is caused by other factors, including psychological and neurological conditions. The Dusky test, while more broadly based than 18 U.S.C. § 4241 also suffers from a number of limitations and has led to conflicting decisions from the Supreme Court and significant uncertainty about its scope. As responsibility for the deficiencies in the current federal law rests almost entirely with the federal judiciary, this paper suggests that federal judges should address the errors of their predecessors and reform the way a defendant’s competence to stand trial is assessed. This can be achieved by the Supreme Court, in an appropriate case, revisiting its decision in Dusky and adopting a test that focuses upon a defendant’s ability to effectively participate in their trial. The effective participation test is derived from jurisprudence from the European Court of Human Rights, and has recently been endorsed by the Law Commission of England and Wales. It is a test that is gaining international traction and is one that would enhance the way the law responds to a significant cohort of defendants in the federal criminal justice system